The encyclopedia of Malaysia the rules of Malaysia - Ahmad Sarji Abdul Hamid (The encyclopedia of Malaysia, 2011)
A fascinating insight into the history and rich heritage of the Malaysian monarchy, its changing role as the country has developed and its constitutional place in Malaysia's multicultural society of today.